2012
DOI: 10.1186/1743-422x-9-309
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of HPV infection in basal cell carcinoma and in perilesional skin biopsies from immunocompetent patients

Abstract: BackgroundThe association between human papillomavirus (HPV) infection and non-melanoma skin cancers (NMSCs) such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) is not yet fully understood. We analysed the prevalence and spectrum of cutaneous beta-HPV types and mucosal/genital HPV types in paired biopsies (tumour and corresponding perilesional skin) obtained from 50 BCC immunocompetent patients. A small group of SCC patients (n=9) was also included. We also evaluated some previously postulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 33 publications
3
44
0
3
Order By: Relevance
“…In one study [14], α-HPV in BCC was positive in 35% of the cases that the high-risk HPV genotypes observed in these patients were HPV 16, 35, 58 and 59. The findings of a research [5] demonstrated that β1-HPVs were the most common HPV types detected in the skin of BCC patients. Moreover, these types and mixed infections are significantly more frequent in tumor samples than in healthy perilesional skin and the results suggested that the types as well as co-infection with more than one viral type could be important in BCC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study [14], α-HPV in BCC was positive in 35% of the cases that the high-risk HPV genotypes observed in these patients were HPV 16, 35, 58 and 59. The findings of a research [5] demonstrated that β1-HPVs were the most common HPV types detected in the skin of BCC patients. Moreover, these types and mixed infections are significantly more frequent in tumor samples than in healthy perilesional skin and the results suggested that the types as well as co-infection with more than one viral type could be important in BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 45 studies reported during 1991 to 2017; two studies were reported in Australia [12,13], one Romania [14], ten USA [15,16,17,18,19,20,21,22,23,24], one Argentina [1], four Netherlands [25,26,27,28], two Spain [8,11], one Brazil [29], one China [30], one UK [31], one Croatia [2], four Iran [9,32,33,34], one North Africa/France [35], one Germany/USA [36], two Greece [37,38], one Sweden/Austria [39], two Germany [40,41], five Italy [5,42,43,44,45], one Russia [46], one Germany/Poland [47], one Norway/Sweden [48] and two Sweden [49,50] (Table I). Fifteen studies were case-control and 30 studies were cross-sectional studies.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations